2007
DOI: 10.1053/j.gastro.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

5-ASA Affects Cell Cycle Progression in Colorectal Cells by Reversibly Activating a Replication Checkpoint

Abstract: Background & Aims-Individuals with inflammatory bowel disease are at risk of developing colorectal cancer (CRC). Epidemiologic, animal, and laboratory studies suggest that 5-aminosalicylic acid (5-ASA) protects from the development of CRC by altering cell cycle progression and by inducing apoptosis. Our previous results indicate that 5-ASA improves replication fidelity in colorectal cells, an effect that is active in reducing mutations. In this study, we hypothesized that 5-ASA restrains cell cycle progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 57 publications
(24 reference statements)
6
68
0
Order By: Relevance
“…The desired therapeutic effects of mesalazine in the intestine require a sufficient intracellular accumulation of the drug (Schwab and Klotz, 2001;Luciani et al, 2007;Koelink et al, 2010). On the basis of our data, it can be concluded that mesalazine is a substrate for the OATP family members OATP1B1, OATP1B3, and OATP2B1.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The desired therapeutic effects of mesalazine in the intestine require a sufficient intracellular accumulation of the drug (Schwab and Klotz, 2001;Luciani et al, 2007;Koelink et al, 2010). On the basis of our data, it can be concluded that mesalazine is a substrate for the OATP family members OATP1B1, OATP1B3, and OATP2B1.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, long-term use of mesalazine in patients with chronic inflammatory bowel disease reduces the risk of development of colorectal cancer in patients with ulcerative colitis (Velayos et al, 2005). Recent in vitro data indicate that an important underlying mechanism of the chemopreventive action of mesalazine is that mesalazine causes cells to reversibly accumulate in the S phase and activate an ataxia telangiectasia-mutated and Rad3-related kinase-dependent checkpoint with subsequent increases in the maintenance of genomic stability and counteracting carcinogenesis (Luciani et al, 2007;Koelink et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reason for this may be that CD patients were younger at diagnosis than UC patients, hence receiving earlier treatment (Jacobsen et al, 2006;Erichsen et al, 2009). Clinical use of acetylsalicylic acid and Five-aminosalicylic acid (5-ASA) in IBD patients could prevent the occurrence of colon cancer, as well as CC (Luciani et al, 2007;Erichsen et al, 2009). On the other hand, PSC is found more rarely in CD (O'Toole et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism by which mesalazine inhibits the generation of frameshift mutations has not yet been characterized. However, studies by the same group have shown that mesalazine can interact with cellular machinery involved in cell-cycle progression [28] . In particular, it has been shown that mesalazine can slow down DNA replication and cell division, thus allowing cells to either repair DNA damage or undergo apoptosis.…”
Section: Effects Of Mesalazine On Replication Fidelitymentioning
confidence: 99%